Interpersonal Diffusion of Health Information: Health Information Mavenism among People Age 65 and over in Japan. Issue 7 (6th June 2020) - Hayashi, Hana; Tan, Andy S.L.; Kawachi, Ichiro; Ishikawa, Yoshiki; Kondo, Katsunori; Kondo, Naoki; Tsuboya, Toru; Viswanath, Kasisomayajula
ABSTRACT: Health information mavens are those who provide and share health information with others via interpersonal communication. We investigated the characteristics of health information mavens among Japanese elderly and whether those who share health information with others via interpersonal communication behave more healthily or report better health status compared to their peers. Data come from a cross-sectional analysis of 27, 414 participants in the Japanese Gerontological Evaluation Study (JAGES) (mean age = 74 years). Mavenism is associated with being female, younger age, higher educational status, and perceived financial condition, as well as larger social networks, higher social support, and media exposure. A higher mavenism score was associated with healthier dietary, and exercise behaviors, but not associated with smoking or alcohol consumption. Mavens were more likely to have a disease and/or report disease symptoms. Health information mavens have the potential to facilitate word-of-mouth communication among older adults, who tend to be more disadvantaged in terms of health information access compared to younger populations.